Effect of the U.S. quantitative easing policy on institutional investor flows of an emerging country - Harshali Damle; Sankarshan Basu (Cogent Economics & Finance, 2020)
The paper investigates the impact of an unconventional monetary policy of the U.S. on the institutional investor flows in India. We assess the relationship between institutional investor flows and market returns before, during and after the U.S. quantitative easing (QE) period. We find a bi-directional Granger causality between domestic institutional investor flows and market returns in the pre QE period. However, the post QE period shows a bi-directional Granger causality between foreign institutional investor flows and market returns. This indicates that the power to influence market returns in India has shifted from the domestic institutional investors to foreign institutional investors during the QE period. Thus, we find evidence for a change in the market dynamics of an emerging country due to spillover effects of an unconventional monetary policy of a foreign country.
Keywords: G15; G23; E58; 330; Institutional investor flows; quantitative easing; emerging economy